AN ASSESSMENT OF CALCITE CRYSTAL GROWTH MECHANISMS BASED ON CRYSTAL SIZE DISTRIBUTIONS - Kile D.E.; Eberl D.D.; Hoch A.R.; Reddy M.M. (My University, 2000)
Calcite crystal growth experiments were undertaken to test a recently proposed model that relates crystal growth mechanisms to the shapes of crystal size distributions (CSDs). According to this approach, CSDs for minerals have three basic shapes: (1) asymptotic, which is related to a crystal growth mechanism having constant-rate nucleation accompanied by surface-controlled growth; (2) lognormal, which results from decaying-rate nucleation accompanied by surface-controlled growth; and (3) a theoretical, universal, steady-state curve attributed to Ostwald ripening. In addition, there is a fourth crystal growth mechanism that does not have a specific CSD shape, but which preserves the relative shapes of previously formed CSDs. This mechanism is attributed to supply-controlled growth.